Letter (copy) : Mr Manuel Egusquiga Urrutia - Bell, Ernest A.
001-0117-001 International 23rd May, 1944. Mr. W. Carillo, Spanish Trade Union Group, Transport House, Smith Square, S.W.I. Dear Mr. Carillo, Mr. MANUEL EGUSQUIGA URRUTIA We wrote on the 25th April to the Home Secretary regarding the case of Mr. Urrutia, and have today received a reply from Mr. Morrison. In that reply it is stated that very careful consideration was given to Mr. Urrutia's case before deciding to maintain in force the provisions of the Aliens (Movement Restriction) Order, 1940 against him. The matter has again been considered following our representations, but the Home Secretary regrets that he can, at the present, find no ground for departing from his previous decision. In accordance with the practice of the Department it is not possible for reasons for this decision to be given. Yours sincerely, Secretary, International Dept. 292/946/1/117